MULTIMODALITY IN THE “THINK GLOBALLY ACT LOCALLY” ENGLISH TEXTBOOK - Annisa Fadhilah Harahap; Indra Hartoyo (Universitas Negeri Medan, 2021)
The objectives of this study were: (1) to identify the components of multimodality that are applied in the textbook entitled